2019
DOI: 10.1155/2019/3689517
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effect of Albendazole on Cutaneous Squamous Cell Carcinoma (SCC) Cells

Abstract: Drug repurposing and/or repositioning is an alternative method to develop new treatment for certain diseases. Albendazole was originally developed as an anthelmintic medication, and it has been used to treat a variety of parasitic infestations. In this study, we investigated the antitumor effect of albendazole and putative action mechanism. Results showed that albendazole dramatically decreased the cell viability of SCC cell lines (SCC12 and SCC13 cells). Albendazole increased apoptosis-related signals, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
(30 reference statements)
2
8
0
Order By: Relevance
“…Supplementary Table 1 ( 4 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 ) summarizes the antitumorigenicity of benzimidazole anthelmintics on cancer cell lines. Benzimidazole anthelmintics inhibit the progression of cancer through a variety of mechanisms.…”
Section: Antitumorigenic Effects Of Benzimidazole Anthelmintics In Camentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementary Table 1 ( 4 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 ) summarizes the antitumorigenicity of benzimidazole anthelmintics on cancer cell lines. Benzimidazole anthelmintics inhibit the progression of cancer through a variety of mechanisms.…”
Section: Antitumorigenic Effects Of Benzimidazole Anthelmintics In Camentioning
confidence: 99%
“…The benzimidazole anthelmintics induced cellular stress through the accumulation of ubiquitylated proteins and increased ROS levels, C/EBP homologous protein (CHOP), activating transcription factor (ATF) 4, and caspase-4/12 as endoplasmic reticulum (ER) stress markers ( 72 ).…”
Section: Antitumorigenic Effects Of Benzimidazole Anthelmintics In Camentioning
confidence: 99%
“…Finally, fenbendazole and albendazole are used commonly in veterinary and human medicine as anti-parasitic and anti-fungal agents (46), mainly by inhibiting tubulin polymerization (47,48). Matched with our drug screen data, recent studies have also shown their anti-tumor activity in different human cancer cells (28,37,38,(49)(50)(51). Further studies will be required to elucidate the common mechanism(s) of action shared by these drugs (if any) in exhibiting preferential cytotoxicity towards highly metastatic prostate cancer cells when compared to the poorly metastatic cells.…”
Section: Discussionmentioning
confidence: 71%
“…In fact, ABZs can induce apoptosis in other ways. According to a study on cutaneous squamous cell carcinoma, ABZs increase apoptosis-related signals by inducing endoplasmic reticulum (ER) stress, and pretreatment with the ER stress inhibitor 4-PBA attenuates ABZ-induced apoptosis ( 56 ). Furthermore, in human leukemia U937 cells, ABZs increase MAPK phosphorylation and upregulate TNF-α expression, thus inducing apoptosis.…”
Section: Progress On the Use Of Benzimidazole Antiparasitic Drugs For Treating Cancermentioning
confidence: 99%